Spectrophotometric Methods for Simultaneous Estimation of Diclofenac Sodium and Rabeprazole in Combined Dosage Form - CHOUDHARY*, BALRAM; GOYAL†, ANJU; L. KHOKRA, SUKHBIR (Asian Journal of Chemistry, 2024)
Two fast, precise and economical spectrophotometric methods havebeen developed for the simultaneous estimation of diclofenac sodiumand rabeprazole in a combined dosage form. Simultaneous determinationof the marketed brands was carried out using simultaneous equationmethod and two wavelength calculation methods. An attempt was madeto estimate both the drugs in a combined dosage form. Methanol wasused as a common solvent for both the drugs. Linearity was observed atboth wavelengths in the concentration range of 10-50 μg/mL for eachdrug. The result of analysis have been validated statistically and also byrecovery studies.